Insight into the defluoridation efficiency of lateritic soil. Issue 4 (29th November 2018) - Oladoja, N. A.; Bello, G. A.; Obisesan, S. V.; Helmreich, B.; Ogunniyi, J. A.; Daramola, O. A.; Bello, H. A.; Anthony, E. T.; Saliu, T. D.
Abstract : The need to explicate the mechanisms that underlies the defluoridation of potable water using lateritic soil necessitated this study. Raw laterite sample was thermally treated at varying temperatures that ranged between 100 ° C and 1000 ° C to determine the effects of thermal treatment on the surficial features and the defluoridation efficiency. The influence of hydrochemistry (i.e., pH, ionic strength, and anionic interference) on the defluoridation efficiency of the lateritic soil was studied. The determination of the effects of thermal treatment on the performance efficiency of the laterites sample showed that the presence of surface hydroxyl group enhanced the defluoridation efficiency. The kinetic analysis of the process showed that the pseudo‐second‐order kinetic equation gave the best description of the process. The evaluation of the influence of ionic strength on the defluoridation efficiency showed that the interaction between the LT0 and the aqua phase F − occurred via inner sphere complex formation. The assessment of the impact of the initial F − solution pH value on the process showed that the possible mode of interaction between the LT0 and the aqua phase F − include electrostatic attraction, ligand exchange, and H‐ bonding. The evaluation of anionic (NO3 −, Cl − PO4 3−, CO3 2−, and SO4 2− ) interference on the process showed that the mode of interaction between the LT0 and the F − occurred via specific adsorption. Laterite can be effectively used in aqua defluoridation, except where the presence of specific interfering ionic species are abundant. © 2018 American Institute of Chemical Engineers Environ Prog, 38:e13107, 2019